2021
DOI: 10.7326/m21-1094
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Risk for Major Bleeding During Extended Oral Anticoagulant Therapy for First Unprovoked Venous Thromboembolism

Abstract: Long-term risk for major bleeding during extended oral anticoagulant therapy for first unprovoked venous thromboembolism: A systematic review and meta-analysis / Khan, F.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 69 publications
3
37
1
1
Order By: Relevance
“…5 In a recent meta-analysis, we determined that the overall incidence of major bleeding during extended anticoagulation for a first unprovoked or weakly provoked VTE was 1.74 events per 100 person-years (95% CI, 1.34-2.20) with vitamin K antagonists (VKA) and 1.12 events per 100 person-years (95% CI, 0.72-1.62) with direct oral anticoagulants (DOACs), with case-fatality rates of 8.3% and 9.7% with VKAs and DOACs, respectively. 6 In contrast, precise estimates for the incidence of recurrent VTE during extended anticoagulation are lacking, and as a result, advising patients on what to expect while receiving extended anticoagulation and estimating the net clinical benefit of extended treatment to guide long-term management remain difficult.…”
Section: Introductionmentioning
confidence: 99%
“…5 In a recent meta-analysis, we determined that the overall incidence of major bleeding during extended anticoagulation for a first unprovoked or weakly provoked VTE was 1.74 events per 100 person-years (95% CI, 1.34-2.20) with vitamin K antagonists (VKA) and 1.12 events per 100 person-years (95% CI, 0.72-1.62) with direct oral anticoagulants (DOACs), with case-fatality rates of 8.3% and 9.7% with VKAs and DOACs, respectively. 6 In contrast, precise estimates for the incidence of recurrent VTE during extended anticoagulation are lacking, and as a result, advising patients on what to expect while receiving extended anticoagulation and estimating the net clinical benefit of extended treatment to guide long-term management remain difficult.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the overall rate of any bleeding in our cohort was 0.65% annually and the major bleeding rate was 0.97 events per 100 patient years. According to a recent published analysis, this rate of bleeding can be considered as low in comparison to the general population of patients treated with anticoagulants ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent meta-analysis of 14 randomized controlled trials and 13 cohort studies, including 9982 patients who received a vitamin K antagonist and 7220 received a DOAC, it has been supported that the incidence of major bleeding was statistically significantly higher among those who had creatinine clearance less than 50 mL/min [ 42 ]. Accordingly, in the present study, we found a correlation between high serum creatinine levels and hemorrhagic complications, but the regression model did not prove that this variable was an independent predictor of hemorrhage.…”
Section: Discussionmentioning
confidence: 99%